Elucidation of Softening Mechanism in Rinse‐Cycle Fabric Softeners. Part 2: Uneven Adsorption—The Key Phenomenon to the Effect of Fabric Softeners. Issue 4 (19th April 2016) - Igarashi, Takako; Nakamura, Koichi; Hoshi, Masato; Hara, Teruyuki; Kojima, Hironori; Itou, Masatsugu; Ikeda, Reiko; Okamoto, Yoshimasa
Abstract: We investigated the actual factor determining the softening effect of a fabric softener. The adsorption area of the softener on model cotton cloths and yarns was identified using bromophenol blue. There was almost no softener at the cross‐points of the yarns in the cloth samples or in the inner part of the yarns. The softening performance was better when there was less softener at the cross‐points of the yarns than when the yarns were evenly covered by the softener. Thus we conclude that the presence of softener at the cross‐points of yarns is not a vital factor in the softening effect. In addition, more softener was found on the outer part of the yarn than the inner part, indicating gradation in the adsorption pattern of the softener. Thus, we propose that more softener is adsorbed on the exposed part of the yarn in a cloth, and the formation of a hydrogen‐bonding network containing bound water is inhibited, thus softening the outer part of the yarn. However, the presence of a small amount of softener in the inner part of the yarn preserves the hydrogen‐bonding network. Favorable elasticity, or bounce, of the yarns and cloth is realized when an appropriate amount of softener is used. Excess softener would reach the inner part of the yarn, reducing the diameter of the core part of the yarn, making the cloth appear wilted.